Perbedaan Motivasi Belajar melalui Pendekatan SAVI dengan Variasi Mengajar Stimulus Materi Dimensi Tiga - Hasibuan, Lilis Harianti (IAIN PADANGSIDIMPUAN, 2019)
Based on the results of the research of the questionnaire score of students learning motivation mathematics then obtained an average of 76 with standard deviation 4.50 in the experimental class applied SAVI approach and average 65 with standard deviation 4.38 on the control class applied Variation Teaching Stimulus. Normality test in experimental class L0 = 0,1296 and Ltabel = 0,1730 then L0 Ltabel (0,1296 0,1730) and at control class L0 = 0,1220 and Ltabel = 0,1730 then L0 Ltabel (0 , 1220 0.1730) so it can be concluded that student questionnaires of both classes are normally distributed. And homogeneity test results obtained Fhitung Ftabel that is (1.073 1.87). Seen from hypothesis test, the data of questionnaire motivation to learn mathematics thitung ttabel (9,13 1,674) which H1 accepted which mean there is difference of motivation learn mathematics between SAVI approach with Variation Teaching Stimulus in cube in class VIII student of SMP Negeri 1 Padang year lessons 2015-2016. The results of observations in the experimental class applied SAVI approach obtained an average of 31.81 with a percentage of 79.52% in both categorize and in the experimental class applied Variations Teaching Stimulus obtained an average of 27.4 with percentage 68, 5% is adequately.